Gandhi prasanga = Gandhi prasang (Basant Behari Jairani Shanti Adhyayan Sansthan, 1998)
Contributed articles on all aspects of life, message, and thoughts of Mahatma Gandhi and attempts to examine Gandhi's technique of change for a peaceful social order.